Sedimentary characteristics of relict deposits on the western South Yellow Sea - Wen, C.; Liu, Jian; Wang, H.; Xu, G.; Qiu, J.; Zhang, J. (2014)
Integrated studies of vertical sedimentary sequences, grain sizes, and benthic foraminifera and ostracoda, in combination with AMS 14C dating, and 210Pb and 137Cs analysis were carried out in three vibracores taken from the area of relict deposits on the western South Yellow Sea. The relict sands, which are about 0.4 m thick, overlie on the Early Holocene coastal marsh or tidal flat deposits with an evident erosional interface in between. The middle and upper parts or sometimes the whole of the relict sands have been reworked under the modern dynamic environment. The sedimentation rate varies between 0.20-0.30 cm year-1. The relict sands show a bimodal grain-size distribution pattern in frequency curves, with a sharp peak in the coarse fraction between 3F and 4F and a secondary peak in the fine fraction of about 7F. Of the benthic foraminiferal and ostracod assemblages, the reworked relict sands are characterized by the mixing of the nearshore euryhaline shallow-water species and deeper water species. The erosional interface at the bottom of the relict sands is considered as a regional ravinement surface formed during the transgression in the Early Holocene due to shoreface retreating landwards. The relict sands were accumulated on the ravinement surface during the transgression in the deglaciation period as lag deposits after winnowing and reworking by marine dynamic processes. And the secondary peak of fine fraction in the frequency curve for the relict sands suggests the input of fine-grained sediments during the reworking process. As the conclusion, the relict sands in the study area are interpreted as a type of reworked relict sediments. © 2014 Science Press, Ocean University of China and Springer-Verlag Berlin Heidelberg.